Palladium-Catalyzed Regioselective Hydroarylation of Ynamides with Aryl Iodides: Easy Synthesis of Various Substituted Enamides Containing Stilbene Derivatives - Wakamatsu, Hideaki; Yanagisawa, Rika; Kimura, Sho; Osawa, Nao; Natori, Yoshihiro; Yoshimura, Yuichi (Synlett, 2017)
Palladium-catalyzed hydroarylation of ynamides has been developed. The desired coupling products were obtained in good yields and with high regioselectivities. Various aryl iodides can be used in this reaction, permitting the syntheses of many different kinds of enamides from ynamides.
Keywords: ynamides; hydroarylation; palladium catalysis; cross-coupling; enamides; arylation